A quantitative risk assessment of a domestic property connected to a hydrogen distribution network. (26th April 2021) - Mouli-Castillo, Julien; Haszeldine, Stuart R.; Kinsella, Kevin; Wheeldon, Mark; McIntosh, Angus
Abstract: The increased reliance on natural gas for heating worldwide makes the search for carbon-free alternatives imperative, especially if international decarbonisation targets are to be met. Hydrogen does not release carbon dioxide (CO2 ) at the point of use which makes it an appealing candidate to decarbonise domestic heating. Hydrogen can be produced from either 1) the electrolysis of water with no associated carbon emissions, or 2) from methane reformation (using steam) which produces CO2, but which is easily captured and storable during production. Hydrogen could be transported to the end-user via gas distribution networks similar to, and adapted from, those in use today. This would reduce both installation costs and end-user disruption. However, before hydrogen can provide domestic heat, it is necessary to assess the 'risk' associated with its distribution in direct comparison to natural gas. Here we develop a comprehensive and multi-faceted quantitative risk assessment tool to assess the difference in 'risk' between current natural gas distribution networks, and the potential conversion to a hydrogen based system. The approach uses novel experimental and modelling work, scientific literature, and findings from historic large scale testing programmes. As a case study, the risk assessment tool is applied to the newly proposed H100 demonstration (100% hydrogen network) project. The assessment includes the comparative risk of gas releases both upstream and downstream of the domestic gas meter. This research finds that the risk associated with the proposed H100 network (based on its current design) is lower than that of the existing natural gas network by a factor 0.88. Highlights: A novel QRA framework is proposed for 100% Hydrogen networks. A comparative approach between hydrogen and natural gas meets regulatory approaches. 100% PE networks with risk mitigation measures meets current network risk levels.